Effect of different dietary protein and energy levels on growth of juvenile Beluga (Huso huso) - Mohseni, M.; Amirkhani, A.; Seyed Hassani, M.H.; Pourali, H.R. (2014)
A 2 × 4 factorial design was conducted to study the effects of dietary protein and energy levels on growth performance of juvenile beluga (Huso huso) with average weight of 49.85 ± 1.64 g. Experiments were conducted with two dietary protein levels (40 and 45%) and four dietary energy level (18.5, 19.8, 21.1 and 22.4 MJ/kg diet) by ratio P/E (18.03 to 24.14 mg/kj). Fish were fed the experimental diets for 110 days. In each of the protein levels (40 and 45%), the feed efficiency, body weight increase, Protein efficiency ratio, specific growth rate, final body weight and total feed intake of fish improved significantly as dietary energy levels increased (P≤ 0.05). Growth of fish fed high- energy diets was significantly higher than those of fish fed low- energy diets at 40 and 45% dietary protein levels (P≤ 0.05). Protein content of carcass increased when dietary protein increased, but there was no significant different (P≥ 0.05) between 40 and 45 % protein. Lipid content of fish fed diet high- energy level was significantly higher than those of fish fed low dietary energy (P≤ 0.05). So the maximum growth and weight (22.4 ± 5.3 gr) was observed in treatment, that were fed diets containing 45% protein & 22.4 mega joule crude energy. Considering that no significant difference were affected for among the diet for the parameters studied, the diet containing 40 % protein, 21 % fat and 21.1 mega Joule crude energy per kilogram diet with a P/E ratio of 20 mg protein per kilo joule from a good quality source is a suitable diet in terms of physiology and economy can be considered a suitable diet to produce maximum growth in juvenile beluga in the weight class 49 to 200g.